슬관절 관절강 외에 발생한 연골지방종 - 김희준(Hee-June Kim); 박경현(Kyeong-Hyeon Park); 이현주(Hyun-Joo Lee); 경희수(Hee-Soo Kyung) (The journal of the Korean Orthopaedic Association, 2022)
연골지방종은 성숙한 연골세포와 지방조직으로 이루어진 드물게 발견되는 양성 간엽종이다. 연골지방종은 구강 내나 유방 등에서주로 발견되는 것으로 보고되며, 슬관절에서 발견되는 경우는 극히 드문 것으로 알려져 있다. 저자들은 좌측 슬관절 전방부에 종괴를 주소로 내원한 60세 여자 환자에서 연골지방종을 경험하였고, 이에 대한 진단과 치료에 대해 문헌 고찰과 함께 보고하고자한다. 자기공명 영상 검사상 슬개건 내측부위에 지방 성분과 석회화된 성분으로 구성된 이종의 양상을 보이는 종괴를 확인하였다. 종괴에 대해 수술적 절제를 시행하였고, 크기는 약 4.5 cm×3 cm×4 cm에 둥근 모양으로 피막에 싸여진 형태였다. 종괴의 후면에서 지방조직과 연골조직이 혼재된 양상의 형태를 보였으며, 병리 조직 소견상 성숙한 지방세포와 초자연골 조직으로 구성된 연골지방종으로 진단하였다. Chondrolipoma is a rare benign mesenchymoma containing mature cartilage and adipose tissues. Chondrolipoma has been encountered mainly in the oral cavity and breast; however, this type of mesenchymoma occurs extremely rarely in the knee area. This paper reports a case of a 60-year-old woman who presented with a two-year history of a palpable mass lesion at the anterior side of the left knee. Magnetic resonance imaging showed a mass lesion adjacent to the medial side of the patellar tendon. The mass had a heterogenous nature, consisting of fat components and calcification. Surgical excision was performed. The size of the excised mass was approximately 4.5 cm×3 cm×4 cm, and it had a round shape and was encapsulated. The posterior part of the mass had a mixed pattern comprised of fat and cartilage tissues. A pathological examination showed that the chondrolipoma was composed of mature adipose and hyaline cartilage tissues. KCI Citation Count: 0